Effects of Aging and Task Prioritization on Split-Belt Gait Adaptation - Vervoort, Danique; den Otter, A. Rob; Buurke, Tom J. W.; Vuillerme, Nicolas; Hortobágyi, Tibor; Lamoth, Claudine J. C. (Frontiers in Aging Neuroscience, 2019)
Background Age-related changes in the sensorimotor system affect gait adaptation, especially when locomotion is combined with a cognitive task. Performing a dual-task can shift the focus of attention and thus require task prioritization, especially in older adults. To gain a better understanding of the age-related changes in the sensorimotor system, we examined how age and dual-tasking affect adaptive gait and task prioritization while walking on a split-belt treadmill. Methods Young (21.5±1.0 y, n=10) and older adults (67.8±5.8 y, n=12) walked on a split-belt treadmill with a 2:1 belt speed ratio, with and without a cognitive Auditory Stroop task. Symmetry in step length, limb excursion, and double support time, and strategy variables swing time and swing speed were compared between the tied-belt baseline (BL), early (EA) and late split-belt adaptation (LA), and early tied-belt post-adaptation (EP). Results Both age groups adapted to split-belt walking by re-establishing symmetry in step length and double support time. However, young and older adults differed on adaptation strategy. Older vs. young adults increased swing speed of the fast leg more during EA and LA (0.10-0.13 m/s), while young vs. old adults increased swing time of the fast leg more (2%). Dual-tasking affected limb excursion symmetry during EP. Cognitive task performance was 5-6% lower during EA compared to BL and LA in both age groups. Older vs. young adults had a lower cognitive task performance (max. 11% during EA). Conclusion Age, but not dual-tasking, affects adaptation strategy during split-belt walking. Young and older adults modified, respectively, the perturbed leg’s timing and speed. This age-related change in adaptation strategy possibly reflects a need to increase gait stability to prevent falling. The decline in cognitive task performance during early adaptation suggests task prioritization, especially in older adults. We conclude that healthy older adults retain the ability to adapt to split-belt perturbations, but interestingly they adapt through a different adaptation strategy. Moreover, challenging motor tasks, like split-belt adaptation, require prioritization between the motor and cognitive task to prevent adverse outcomes. This suggests that task prioritization and adaptation strategy should be a focus in fall prevention interventions.